2005
DOI: 10.1529/biophysj.104.055129
|View full text |Cite
|
Sign up to set email alerts
|

The Geometry of the Flux Cone of a Metabolic Network

Abstract: The analysis of metabolic networks has become a major topic in biotechnology in recent years. Applications range from the enhanced production of selected outputs to the prediction of genotype-phenotype relationships. The concepts used are based on the assumption of a pseudo steady-state of the network, so that for each metabolite inputs and outputs are balanced. The stoichiometric network analysis expands the steady state into a combination of nonredundant subnetworks with positive coefficients called extremal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 32 publications
0
70
0
Order By: Relevance
“…Using ideas from stoichiometric network analysis [10], it is possible to analyze the system dynamics in flux space instead of concentration space and to represent the space of steady states with a combination of subnetworks. The subnetworks form a convex cone in flux space [68]. There are techniques for decomposing that cone and limiting the search for Hopf bifurcations to lower dimensional facets [22].…”
Section: Further Applications In Chemistry and The Life Sciencesmentioning
confidence: 99%
“…Using ideas from stoichiometric network analysis [10], it is possible to analyze the system dynamics in flux space instead of concentration space and to represent the space of steady states with a combination of subnetworks. The subnetworks form a convex cone in flux space [68]. There are techniques for decomposing that cone and limiting the search for Hopf bifurcations to lower dimensional facets [22].…”
Section: Further Applications In Chemistry and The Life Sciencesmentioning
confidence: 99%
“…If one is only interested in generating the flux space fulfilling (11), the more reasonably choice is a minimal generating set, a smallest set of vectors holding the property (Urbanczik, 2005). Unfortunately this set is not unique in the general case.…”
Section: Generate the Flux Spacementioning
confidence: 99%
“…In fact, it has been recently shown that the set of extreme currents (ECS) coincide with the set of elementary modes, which will be introduced below, when it is translated to the original vector-space (Wagner, 2005)-when computing the first a set of r spurious cycles appear (pathways formed by the forward and backward reaction of each reversible flux); however, these pathways are not considered meaningful (Schilling, 2000) and they disappear when the ECS are expressed in the original vectorspace R n .…”
Section: Extreme Currentsmentioning
confidence: 99%
See 2 more Smart Citations